2008
DOI: 10.1159/000109589
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Cutaneous Vasculitis in Adult Patients from the Farwaniya Region of Kuwait

Abstract: Objective: To determine the clinical profile, etiologic factors, disease associations, and the laboratory profile of adult patients with cutaneous leukocytoclastic vasculitis (LV) presenting to the Dermatology Department at Farwaniya Hospital, Kuwait. Subjects and Methods: The medical records of 57 adult patients (>18 years) with biopsy-proven cutaneous LV from January 2004 to June 2006 at Farwaniya Hospital were reviewed. Results: Of the 57 patients studied, 21 (36.8%) were classified as having primary cutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
8
1
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 38 publications
11
8
1
19
Order By: Relevance
“…15,44 One study found that in an adult population with LCV, IgA deposition within dermal vessels was most often secondary to druginduced hypersensitivity vasculitis rather than HSP. 45 Helander, DeCastro, and Gibson 4 reported that out of 92 cases with cutaneous IgA vascular deposits and impression of vasculitis on DIF (not all showed LCV histologically), HSP was diagnosed in only 24% (other diseases being erythema nodosum, venous stasiserelated skin disease, cryoglobulinemia, coagulopathic vasculopathies, and livedoid vasculitis). They found that 9% of IgA vasculitis cases had 35,38,43,46 and in 18% to 93% of patients with alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…15,44 One study found that in an adult population with LCV, IgA deposition within dermal vessels was most often secondary to druginduced hypersensitivity vasculitis rather than HSP. 45 Helander, DeCastro, and Gibson 4 reported that out of 92 cases with cutaneous IgA vascular deposits and impression of vasculitis on DIF (not all showed LCV histologically), HSP was diagnosed in only 24% (other diseases being erythema nodosum, venous stasiserelated skin disease, cryoglobulinemia, coagulopathic vasculopathies, and livedoid vasculitis). They found that 9% of IgA vasculitis cases had 35,38,43,46 and in 18% to 93% of patients with alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…La VLC peut survenir à tout âge avec une prédominance de l'âge adulte [1]. En se référant aux données de la littérature, l'âge moyen des patients varie de 42,5 ans à 60 ans [2, 3, 5]. L'âge moyen de nos patients était de 47 ans.…”
Section: Discussionunclassified
“…L'âge moyen de nos patients était de 47 ans. Selon les publications, le sexe ratio hommes/femmes au cours de la VLC varie de 0,7 à 1,8 [2, 3, 5]. Dans notre étude, il existe une prédominance féminine avec un sex-ratio hommes/femmes de 0,6.…”
Section: Discussionunclassified
See 2 more Smart Citations